Організація харчування учнів шкіл Донбасу в 60-70-ті роки ХХ ст. - Лаврут, О.О. (Історичний архів. Наукові студії, 2015)
Протягом 60–70-х років минулого століття заклади освіти накопичили значний досвід з питання організації харчування учнів шкіл УРСР. На прикладі регіональних особливостей автор охарактеризувала зазначену проблему. Діти харчувались у різних типах їдалень. Це було зумовлене особливостями кількісного та якісного характеру, місцевими та регіональними умовами. Організацію харчування учнів контролювали місцеві та державні органи влади. На протяжении 60–70-х годов прошлого века учреждения образования накопили большой опыт по вопросу организации питания учеников школ УССР. На примере региональных особенностей автор охарактеризовала указанную проблему. Дети питались в разных типах столовых. Это было обусловлено особенностями количественного и качественного характера, местными и региональными условиями. Организацию питания учеников контролировали местные и государственные органы власти. The effectiveness of the educational process depends not only on the logistical and methodological support, but also the organization of nutrition students of secondary schools. This is due to the fact that children spend a significant amount of time in schools. In order to preserve their healthy potential need to take care of basic compliance requirements that need proper attention.
During 1960–70 years in the former USSR has accumulated considerable experience on the subject. The study will help to improve its catering students in modern conditions of operation of educational institutions. During this period worked different types of dining. Among them were: dining, buffets, additional non Rose points rooms, food. It was uneven. Emphasis was carried out in the city, then – rural institutions.
At a high level took place catering children in the cities Chistyakov, Kramatorske, Slavic, Uzhgorod (which explained the cooperation of industry and educational institutions) areas: Maryinsky, Volnovakha, Snizhnyans’ka (which were overwhelmingly agricultural). At a high level took place catering children in the cities Chistyakov, Kramatorske, Slavic, Uzhgorod (which explained the cooperation of industry and educational institutions) areas: Maryinsky, Volnovakha, Snizhnyans’ka (which were overwhelmingly agricultural).
However, some schools operate without cafeterias, buffets had close, which was a limited range of dishes. So focused on the timely opening of canteens, snack bars, compiling weekly breakfast menu and lunch. In school coffee shops selling milk, sour-milk products, sandwiches, salads, fruit juices and hot drinks. In turn, the food industry had to produce a sufficient amount of school products range in small packaging. To preserve food dining, buffets and handouts were provided necessary technological, refrigeration, cooking implements and utensils; carried out their repairs. Places to Eat ukomplektovuvalys skilled cooks and their assistants.
Important for the functioning of nutrition and dining pupils remained create food reserves, in particular – vegetables.
After failure hygiene standards children can suffer from various diseases. Public authorities responded to the incident. Often teachers and medical staff did not pay enough attention to this.
Рroviding and organization of feed of students of schools products during the noted period was at high level. The prospect of our research will be become by finding out of the indicated question during the next periods of development of school in Ukrainian SSR.